Reduced Resting State Neural Activity in the Right Orbital Part of Middle Frontal Gyrus in Anxious Depression - Zhao, Peng; Yan, Rui; Wang, Xinyi; Geng, Jiting; Chattun, Mohammad Ridwan; Wang, Qiang; Yao, Zhijian; Lu, Qing (Frontiers in Psychiatry, 2020)
Background: Anxious depression(AD)，which is generally recognized as a common clinical subtype of major depressive disorder (MDD), holds distinctive features compared with unanxious depression(UAD). However, the neural mechanism of AD is still remains unrevealed. To give insight to it, we compared resting-state functional magnetic resonance amplitude of low-frequency fluctuation (ALFF) and functional connectivity (FC) between AD and UAD patients. Method: The data were collected from 60 AD patients, 38 UAD patients and 60 matched healthy controls. The ALFF and seed-based FC were examined. Pearson correlations were computed between ALFF/FC and clinical measures. Results: In Comparison with the UAD group, the ALFF value of the right orbital part of middle frontal gyrus(RO-MFG) decreased in AD group. Specifically, the ALFF values of the RO-MFG were negatively correlated with retardation factor scores in AD group (r=-0.376, p=0.003). Conclusions: AD patients exhibited disturbed intrinsic brain function compared with UAD patients. The decreased activity of the RO-MFG is indicative of the alterations involved in the neural basis of AD.